2009
DOI: 10.1016/j.aop.2008.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian methods for parameter estimation in effective field theories

Abstract: We demonstrate and explicate Bayesian methods for fitting the parameters that encode the impact of short-distance physics on observables in effective field theories (EFTs). We use Bayes' theorem together with the principle of maximum entropy to account for the prior information that these parameters should be natural, i.e. O(1) in appropriate units. Marginalization can then be employed to integrate the resulting probability density function (pdf) over the EFT parameters that are not of specific interest in the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
96
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(99 citation statements)
references
References 52 publications
3
96
0
Order By: Relevance
“…Given the LECs, the prediction is exactly known, while we have shown that the theoretical uncertainty is a multivariate Gaussian. Assuming that the experimental noise is also a Gaussian For the special case of the fully correlated coefficients and a finite k max , we could instead integrate in each (univariate) unknown coefficient [30,19] The form of (B.42) is potentially advantageous when k max − k is small and Σ exp is diagonal, since the size of the matrix inversion for A is only (k max − k) × (k max − k) rather than N d × N d as in (B.33).…”
Section: Appendix B3 Interlude: Fun With Gaussian Integrals Delta mentioning
confidence: 99%
“…Given the LECs, the prediction is exactly known, while we have shown that the theoretical uncertainty is a multivariate Gaussian. Assuming that the experimental noise is also a Gaussian For the special case of the fully correlated coefficients and a finite k max , we could instead integrate in each (univariate) unknown coefficient [30,19] The form of (B.42) is potentially advantageous when k max − k is small and Σ exp is diagonal, since the size of the matrix inversion for A is only (k max − k) × (k max − k) rather than N d × N d as in (B.33).…”
Section: Appendix B3 Interlude: Fun With Gaussian Integrals Delta mentioning
confidence: 99%
“…We therefore use a so-called prior-fit and modify our χ 2 to, see e.g. [53], Overall the prior-fit method behaves stable, since the minimum is not as flat as without the additional terms and all 19 LECs can be fitted quite precisely. However, we have to pay attention to choosing the errors ∆b i and ∆d i .…”
Section: Unconstrained Fitsmentioning
confidence: 99%
“…Therefore, we try to constrain all the LECs to natural values following ref. [57] which discusses the use of the Bayesian method in effective field theories. Following Table 5.…”
Section: Jhep11(2015)058mentioning
confidence: 99%